2020
DOI: 10.3389/fnins.2020.571312
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of the Duration of the Initial Self-Control Task Within the Sequential-Task Paradigm: Effect on Exercise Performance

Abstract: Self-control exertion on an initial task has been associated with impaired performance on subsequent physical tasks also requiring self-control; an effect suggested to be mediated by changes in perceptions of pain and motivation. However, the effects of spending longer on the initial self-control task are unknown. This study, therefore, explored the potential for the duration of the initial self-control task to influence subsequent physical performance, perceptions of pain, and perceived motivation; particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 49 publications
(99 reference statements)
0
19
3
Order By: Relevance
“…In general, it has to be acknowledged that there is no broad consensus which tasks are valid self-control tasks and how long self-control needs to be invested in a given task in order to actually induce ego depletion [see also Englert ( 2017 ), e.g., Boat et al ( 2020 )]. For instance, it remains unclear how long a Stroop task should ideally last or how many trials it should contain (e.g., Wolff et al, 2021 ).…”
Section: Replication Requires Appropriate Operationalizationmentioning
confidence: 99%
“…In general, it has to be acknowledged that there is no broad consensus which tasks are valid self-control tasks and how long self-control needs to be invested in a given task in order to actually induce ego depletion [see also Englert ( 2017 ), e.g., Boat et al ( 2020 )]. For instance, it remains unclear how long a Stroop task should ideally last or how many trials it should contain (e.g., Wolff et al, 2021 ).…”
Section: Replication Requires Appropriate Operationalizationmentioning
confidence: 99%
“…One very likely reason for this research gap is that research from sports and exercise has primarily focused on the self-control demands of completing effortful and difficult tasks, like performing a sprint start ( Englert et al, 2015 ), persisting for as long as possible in an endurance task ( Boat et al, 2020 ), or adhering to an exercise regimen ( Englert and Rummel, 2016 ). This focus makes intuitive sense, since self-control is per definition linked to the notion of effort ( de Ridder et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…We would also like to address the fact that the depletion condition took significantly longer to finish the Stroop task than the control condition. This matter seems especially important, as a recent study by Boat et al (2020) revealed that longer Stroop task durations were related to lower performance in a subsequent self-control task. However, in the current study we did not find an effect of the different Stroop task durations on the veracity ratings.…”
Section: Discussionmentioning
confidence: 99%